2006
DOI: 10.1073/pnas.0600078103
|View full text |Cite
|
Sign up to set email alerts
|

Selection of cervical keratinocytes containing integrated HPV16 associates with episome loss and an endogenous antiviral response

Abstract: Integration of high-risk human papillomavirus (HRHPV) into the host genome is a key event in cervical neoplastic progression. Integration is associated with deregulated expression of the viral oncogenes E6 and E7 and acquisition of a selective growth advantage for cells containing integrants. Overexpression of the viral transcriptional regulator E2 from heterologous promoters has an inhibitory effect on transcription from integrated HRHPV. Therefore, we hypothesized that loss of E2-expressing episomes from cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
153
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 32 publications
10
153
0
6
Order By: Relevance
“…43 We demonstrated the integrated form of HPV 16 in all of the carcinoma specimens and significantly increased HPV 16 integration in cervical carcinoma compared with CIN 2/3, supporting the notion that HPV 16 integration into the host genome is an important step of carcinogenesis. 17,18 In most published studies of cervical carcinoma, the integrated forms of HPV 16 were also observed in either all or a majority of the specimens. 42,43 AriasPulido et al 22 recently conducted a study of formalin-fixed paraffin-embedded as well as fresh cervical specimens using qRT-PCR and reported a relatively low proportion of the integrated type of HPV 16 in carcinoma in situ (30.3%) and in invasive carcinoma (60.9%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…43 We demonstrated the integrated form of HPV 16 in all of the carcinoma specimens and significantly increased HPV 16 integration in cervical carcinoma compared with CIN 2/3, supporting the notion that HPV 16 integration into the host genome is an important step of carcinogenesis. 17,18 In most published studies of cervical carcinoma, the integrated forms of HPV 16 were also observed in either all or a majority of the specimens. 42,43 AriasPulido et al 22 recently conducted a study of formalin-fixed paraffin-embedded as well as fresh cervical specimens using qRT-PCR and reported a relatively low proportion of the integrated type of HPV 16 in carcinoma in situ (30.3%) and in invasive carcinoma (60.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In the second step of our screening process, specimens positive for b-globin were screened for HPV by using GP5 þ /GP6 þ consensus primermediated PCR, which can detect 14 oncogenic HPV genotypes, including the eight major oncogenic HPV types (16,18,31,33,35,45,52, and 58). PCR was performed according to Jacobs et al 32 A 25-ng aliquot of genomic DNA was added to the PCR master mixture, which contained 1 Â PCR buffer, 200 mM each deoxynucleoside triphosphate, 200 nM primer, 3.5 mM MgCl 2 , and 2.5 U of AmpliTaq Gold DNA polymerase.…”
Section: Hpv Dna Testing Using Consensus Primer-mediated Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Infected cells with episomal HPV are cleared after exposure to IFN-β, but cells with integrated HPV-DNA are resistant to this antiviral effect (Pett et al, 2006). T-cell response to E2 and E6 are lost or reduced in CIN 3 and carcinoma invasive.…”
Section: Mechanism Of Immune Evasionmentioning
confidence: 99%